Early ontogeny of the African bony-tongue (Heterotis niloticus) and the effect of Artemia and rotifer live feeds on larval digestive enzyme activity and performance - Ofori-Darkwah, Prince; Adjei-Boateng, Daniel; Edziyie, Regina Esi; Agbo, Nelson Winston; Lund, Ivar (Frontiers in Aquaculture, 2024)
High larval and fry mortality has been a major challenge to the commercial culture of the African bony-tongue (Heterotis niloticus). Research indicates inadequate feeding as the possible cause of the high mortality of larvae/fry grown in captivity. An experiment was conducted to first describe the developmental stages of H. niloticus eggs and larvae until schooling, 6 days after-hatch (DAH) at 26°C. The morphological development, survival, growth (weight gain and length), and swimming behavior of the larvae were monitored. In a second set-A follow-up a feeding trial was conducted with H. niloticus fry from 6-27 DAH and involving four treatments: Artemia nauplii; A combined ration of 50% Artemia nauplii and 50% rotifers (w/w); rRotifers; -and fry notno feed. The activity of three digestive enzymes (trypsin, lipase, and amylase) were determined assessed in fry exposed to the live feed treatments. At hatching, the larvae had a large, vascularized yolk sac filled with yolk platelets, which occupied about one-third of the total body length of the abdominal cavity. Yolk platelet reabsorption started 1 DAH and was completely absorbed 6 DAH. Metamorphosis was completed at 6 DAH and schooling behavior observed. For the feeding trial, the fry that received Artemia nauplii had the fastest development until 27 DAH. Similarly, the survival rate was considerably higher in fry fed Artemia nauplii, than those that received a combination of Artemia nauplii and rotifers, or only rotifers. Overall, the survival rate for fry fed Artemia nauplii and larvae co-fed were 72.7±0.9% and 41.2±3.3%, respectively. Fry did not survive until 27 DAH in the rotifer-fed and non-fed treatments. The digestive enzyme activity differed significantly (p< 0.05) between treatments and sampling dates. All digestive enzymes were detectable at the onset of mouth opening (5DAH) and fluctuated through the 7 and 9 DAH. A lower enzyme activity were observed when the fry were subjected to starvation or the rotifer treatment. Results obtained in this studyindicate that Artemia nauplii is best live feed organism for H. niloticus larviculture. give prospects for future aquaculture success of this species